2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20180142
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hirsutism on the quality of life of Indian women

Abstract: INTRODUCTIONHirsutism is defined as excessive male pattern hair growth in a female. 1 The prevalence of hirsutism is 10% in women of child bearing age and is influenced by genetic and racial factors.2 It is cosmetically concerning for women and can affect the self-esteem significantly. 3Women with hirsutism have social phobia, insecurity about interpersonal relationships, shattered confidence and profound psychological sequlae. 4 Quality of life is defined as "the individuals" perceptions of their position in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…mostly affected subdivisions of life quality were found to be daily activities (such as shopping, choice of clothes or housekeeping) and symptoms and feelings (such as itchy and sore skin, embarrassment) in the literature. 15,17,25,27,29 Our results were in concordance with these literature reports with the highest score in daily activities (31%) followed by symptoms and feelings (29%). Self-rated hirsutism scores were found to be higher than physician rated scores in previous studies 14 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…mostly affected subdivisions of life quality were found to be daily activities (such as shopping, choice of clothes or housekeeping) and symptoms and feelings (such as itchy and sore skin, embarrassment) in the literature. 15,17,25,27,29 Our results were in concordance with these literature reports with the highest score in daily activities (31%) followed by symptoms and feelings (29%). Self-rated hirsutism scores were found to be higher than physician rated scores in previous studies 14 .…”
Section: Discussionsupporting
confidence: 91%
“…The average DLQI scores reported in the literature vary between 5.5 and 17.4. 10,15,25,26,28 While mean DLQI score in our patients is similar to some studies, 7,17,18,26,28,29 it is lower than some of the DLQI scores in previous studies. 15,25,27 The differences in DLQI scores in previous studies, including ours, were suggested to result from differences in the mean mFG scores.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation